Effects of Dictation On the Written Word Spelling of Junior Secondary School JSS III Students in Jigawa State (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study attempted to investigate the effects of dictation on the written word spelling of Junior Secondary School JSS III students in Jigawa state. The study was motivated by the difficulty faced by learners of English as L2 in spelling of words especially the irregular spelling in their essays. Two research questions were set and answered. The target population was the JSS III students in Jigawa State. The study was conducted in the 2022/2023 academic session. Experimental research design was adopted for the study. 150 students were randomly sampled from two JSS within two senatorial districts in the state and were equally assigned as experimental and control groups. The instruments used were the selected and modified words from JSS course books which were the English words selected and modified from JSS course books which were used for the pre-test and post-test respectively. The research questions were answered in form of table showing the frequency and percentage. The major findings of the study showed that 48% of the participants in the experimental group spelt more irregular words while only 33% spelt the same words in the control group after the treatment. The study recommended that teachers of English as a second language should be trained so that they would be more sensitive to dictation strategies that enable them to teach JSS students to acquire ability of spelling more regular and irregular words.